Source‐transport inversion: An application of geophysical inverse theory to sediment transport in Monterey Bay, California - Tait, James F.; Revenaugh, Justin (Journal of Geophysical Research, 1998)
Application of forward coastal sediment transport models in situations involving large temporal and spatial scales or topographically complex environments can be highly problematic since the distribution of hydrodynamic parameters is rarely adequately known. Where rocky topography is present, flow patterns may be altered and sediments trapped by topographic barriers. A frequently employed approach to these problems is the application of the statistical technique known as empirical orthogonal function (EOF) analysis. One limitation of EOF analysis of grain size and mineralogical data is that EOF is a purely geometric technique which does not allow incorporation of a priori knowledge we may have regarding the physical environment. In fact, there is no guarantee that a meaningful physical interpretation of the results of an EOF analysis actually exists. This is not true of geophysical inverse theory, which is capable of incorporating diverse forms of information and is not limited to purely geometric manipulations of data. We have formulated an inverse theoretical approach to study sediment transport which we call STI, short for source-transport inversion. STI relaxes the nonphysical assumption of orthogonal endmembers and can handle many forms of a priori information. STI has been developed initially in the context of modeling the sediment supply and dispersal system of Monterey Bay, California. Using the geographical distribution of heavy mineralogy data, significant sources are identified and sediments traced from those sources along transport pathways. Model results are encouraging both in terms of goodness of fit between model and data and in terms of the agreement of model results with the sediment sourcing and dispersal patterns inferred in previous studies. Model results indicate that beach sediments are primarily derived from the open coast north of the bay, that a littoral cell boundary exists in the center of the bay at Moss Landing, and that beach deposits produced by paleolittoral drift during a sea level low stand lie along the 100-m isobath. Copyright 1998 by the American Geophysical Union.
Keywords: Bryophyta; USA, California, Monterey Bay; bottom topography effects; dept.esc; sediment transport; shelf dynamics